1987
DOI: 10.1111/j.1440-1673.1987.tb01789.x
|View full text |Cite
|
Sign up to set email alerts
|

“A Case of Autosomal Recessive Form of Cranio‐Metaphyseal Dysplasia with Unusual Features and with Bone Fragility”

Abstract: FIGURE I -Lack of eruption and enamel hypoplasia.Australasian Radiology, Vol. XXXI, No. I . February, I987 osteomyeiitis were present from the age of 28 months. The bone fragility was observed from the age of 4-5 years, when an apparently sponthat of pyknodysostosis can be noted: large and prominent front in contrast with facial hypoplasia. prominent and beaked nose. Deformity of the left cheek is due to mandibular osteomyelitis.Accepted for publication on 16th December, 1985.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Craniometaphyseal dysplasia shows a combination of cranial sclerosis and metaphyseal undermodeling, but adult body height is normal: Bone fragility or osteopathia striata are not usually present in this condition [Gorlin et al, 1970;Beighton et al, 1979;Spranger, 1979]. Ventruto et al [1987] reported on a woman with this condition who had bone fragility and short stature but who lacked osteopathia striata. Culver and Thumasathit [1972] described a girl with cranial sclerosis, osteopathia striata, and mild metaphyseal splaying, but she had no bone fragility.…”
Section: Discussionmentioning
confidence: 99%
“…Craniometaphyseal dysplasia shows a combination of cranial sclerosis and metaphyseal undermodeling, but adult body height is normal: Bone fragility or osteopathia striata are not usually present in this condition [Gorlin et al, 1970;Beighton et al, 1979;Spranger, 1979]. Ventruto et al [1987] reported on a woman with this condition who had bone fragility and short stature but who lacked osteopathia striata. Culver and Thumasathit [1972] described a girl with cranial sclerosis, osteopathia striata, and mild metaphyseal splaying, but she had no bone fragility.…”
Section: Discussionmentioning
confidence: 99%